Neuromuscular efficiency of the knee joint muscles in the early-phase of strength training: effects of antagonist’s muscles pre-activation - Cardoso, Euler Alves (2018)
It was our objective tTo compare the neuromuscular efficiency (NME) adaptations between resistance exercise methods (with and without pre-activation of the antagonist’s muscles) after six-weeks training. This randomized controlled trial assigned forty-nine men (mean age 20.9 ± 2.2 years; height 1.80 ± 0.1 m; body mass 75.0 ± 8.2 kg) into two groups: 1) Reciprocal Training group (RT, concentric knee flexion immediately followed by concentric knee extension at 60°.s-1); and Conventional Training (CT, concentric knee extension exercise). Both training adopted three sets, 10 repetitions at 60°.s-1, 2 days/week for 6 weeks. NME of knee extension and flexion were assessed pre and post-training. The groups were similar at baseline, for all variables. We found significant effects on NME only for the rectus femoris muscle in the RT group (ES = 0.31; 95%CI [0.30-0,92]; p<0.01). There were no significant differences at NME pre- and post-training in CT and Total Work did not differ between groups. Reciprocal training provided better neuromuscular efficiency, but effects were limited to the rectus femoris muscle. The small effect sizes suggest caution in the results.